Assessing cultural awareness in reading texts at a university in Libya - Khalefa Alsadek Albakoush, 1978-, author; Norazman Abdul Majid, supervisor; Fakulti Pendidikan (2013)
Thesis (Ph.D (Pengajaran Bahasa Inggeris Sebagai Bahasa Kedua)) - Universiti Teknologi Malaysia, 2013